Managing irritable bowel syndrome via gut-brain axis modulation and antispasmodic - anxiolytic dual action: an Indian expert panel review - Lakhtakia, Sundeep; Katrevula, Anudeep V.; Katukuri, Goutham R. (International Journal of Research in Medical Sciences, 2025)
Irritable bowel syndrome (IBS) is a complex, multifactorial functional gastrointestinal disorder characterized by recurrent abdominal discomfort, altered bowel habits, and a high prevalence of psychological comorbidities, particularly anxiety. In the Indian clinical landscape, IBS remains underdiagnosed, largely due to symptom overlap with other gastrointestinal conditions and the lack of standardized diagnostic protocols. Anxiety significantly contributes to the exacerbation of IBS symptoms, primarily through dysregulation of the gut-brain axis. This manuscript explores the evolving paradigm of IBS diagnosis and management in India, with a particular focus on the therapeutic potential of antispasmodic-anxiolytic combinations. Among these, the fixed-dose combination of clidinium and chlordiazepoxide stands out for its dual mechanism of action, offering both peripheral antispasmodic and central anxiolytic effects. This makes it especially effective in managing IBS cases where psychological stress is a key aggravating factor. Unlike conventional monotherapies, this combination addresses both visceral hypersensitivity and the psychological dimensions of IBS, thereby enhancing symptom control in stress-amplified presentations. The manuscript also explores recent advancements in digital health tools, biomarker discovery, and precision medicine approaches that are reshaping IBS diagnostics and enabling more personalized treatment strategies. Insights from real-world clinical practice and patient profiling underscore the importance of individualized, multimodal management integrating pharmacologic interventions with lifestyle and behavioural therapies.